ANALISIS PUSTAKA MENGENAI METODE TIMELINE DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI JENJANG SEKOLAH MENENGAH - Muhammad Rizqi; Abdullah Abdullah (TABYIN: JURNAL PENDIDIKAN ISLAM, 2026)
The learning of Islamic Cultural History (SKI) plays a crucial role in shaping students' character and historical insight across all levels of education. Nevertheless, limitations in the teaching methods often impede students' comprehension of historical event sequences. This study aims to conduct a literature review on the application of the timeline method in SKI learning. A library research method was employed by analyzing various sources related to the use of timelines in history education, particularly within SKI contexts. The findings reveal that the timeline method enhances students' chronological understanding, strengthens memory retention, and promotes active engagement during lessons. This study recommends systematic integration of the timeline method at every educational level to optimize the effectiveness of SKI instruction.